Clarifying Some Misconceptions About Stock Market Economies - Milne, Frank; Shefrin, Hersh M. (Quarterly Journal of Economics, 1984)
Frank Milne, Hersh M. Shefrin; Clarifying Some Misconceptions About Stock Market Economies*, The Quarterly Journal of Economics, Volume 99, Issue 3, 1 Augu